The impact of migration on a regulated rental market - Adam Alexander Tyrcha (REGION, 2020)
Throughout the 20th century, the Swedish rental market has generally been heavily regulated, with both a rental queue in place, as well as generally fixed rents, with limited ability to vary these. Though these systems remain in place, in the 21st century, a number of deregulatory measures have been taken. Meanwhile, evolving migration flows and strong humanitarian migration in particular have continued. These developments combined mean that now more than ever, impacts of migration on the rental housing market are increasingly likely. This paper investigates the relationship between foreign-born and internal migration and rents on the housing market. Findings suggest that foreign-born migration, and refugees in particular, impact rents, especially in major cities.
Keywords: J61; R23; R31; R11; 330; immigration; internal migration; housing; rents; rental market